Modele badań marketingowych w przedsiębiorstwie na rynku europejskim - Sojkin, Bogdan (Models of Marketing Research in An Enterprise on the European Market, 2006)
Essence and purposed of the marketing research have not changed, but new solutions offered by the techniques and the technologies and which are used in the research changed its form, procedure and organization. The standard solutions of the research conduct are replaced by newer and more effective ones. Apart from the classical solutions of marketing research in an enterprise like centralized decentralized solutions, the new ones appear which propose full outsourcing and different indirect ways of dealing. These include a redefinition of the model of marketing research, of the marketing researchers and the on-going nature of marketing research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 143-151